A novel non-sense variant in the OFD1 gene caused Joubert syndrome - Li, Chen; Wang, Xingwang; Li, Fake; Ding, Hongke; Liu, Ling; Xiong, Ying; Yang, Chaoxiang; Zhang, Yan; Wu, Jing; Yin, Aihua (Frontiers in Genetics, 2023)
Background: Joubert syndrome (JBS) is a rare neurodevelopmental disorder associated with progressive renal, liver, and retinal involvement that reveals heterogeneity in both clinical manifestations and genetic etiology. Therefore, it is difficult to make a definite prenatal diagnosis. Methods: Whole-exome sequencing and Sanger sequencing were performed to screen the causative gene variants in a suspected JBS family. RNA-seq and protein model prediction were performed to clarify the potential pathogenic mechanism. A more comprehensive review of previously reported cases with OFD1 variants is presented and may help to establish a genotype–phenotype. Results: We identified a novel nonsense variant in the OFD1 gene (c.2848A>T, p.K950*). Sanger sequencing confirmed cosegregation among this family. RNA-seq confirmed that partial degradation of mutant transcripts, which was caused by the NMD mechanism, may explain the reduction in the proportion of mutant transcripts. Protein structure prediction of the nonsense variant transcript revealed that this variant may lead to a change in the OFD1 protein structure. Conclusion: The genetic variation spectrum of JBS10 caused by OFD1 was broadened. The novel variants further deepened our insight into the molecular mechanism of the disease.